Teatralizacja w edukacji początkowej. Kreatywny nauczyciel, kreatywny uczeń - Matecka, Anna (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
The subject of the considerations undertaken in this article is the presentation of the theatrical method that I used during the classes at the stage of initial education. The first part of the article presents the genesis of the term theatralization, and attempts to formulate a definition of this term in relation to the space of educational activities. This part also presents theatricalisation as an activating didactic and educational method along with tools that allow it to be studied. The second part of the article presents the benefits that can be gained by students thanks to learning through the theatrical method. The last part of the article is a description of the author’s experiences in this area and some examples of suggestions for use during the classes.